Connecting older grandmothers raising grandchildren with community resources improves family resiliency, social support, and caregiver self-efficacy. (4th May 2019) - Pandey, Abhishek; Littlewood, Kerry; Cooper, Larry; McCrae, Julie; Rosenthal, Michelle; Day, Angelique; Hernandez, Liliana
ABSTRACT: Custodial grandparenting can be especially challenging for older grandmothers facing age specific issues. Kinship navigator programs are social service delivery programs intended to inform grandparents and other relatives raising children about available resources and services, provide information specific to their individual needs, and help families navigate service systems. Our study utilizes self-report data from one kinship navigator federal demonstration project, which used a randomized control trial, to examine demographic characteristics for grandmothers under and over 55 years of age, whether grandmother caregivers (≥55 years) improve family resilience, social support, and caregiver self-efficacy, and which interventions improved outcomes for grandmothers (≥55 years). Each participant was randomly assigned to one of four groups: Usual Care (traditional child welfare services), Standard Care (family support and case management), Peer-to-Peer Care Only, and Full Kin Tech Care (peer navigators with computer access and interdisciplinary team). Thirty-nine percent of grandmothers (55-75 years) were mostly living in poverty, predominantly Caucasian, with 36% identifying as African American/Black, with at least one to two children at home. Repeated-measures ANOVAs for each subscale showed statistically significant within- and between-group differences for Family Functioning, Social Supports, Concrete Supports, Child Development, and Nurturing and Attachment, with the exception of Usual Care, which showed a decline in protective factors consistently across subscales. Future research with kinship families could qualitatively examine the experiences for older women in navigator programs and replication of kinship navigator programs could build capacity in data collection and maintenance systems to gain better perspective about how systems of care impact families.